2013
DOI: 10.9744/nirmana.14.1.36-46
|View full text |Cite
|
Sign up to set email alerts
|

Designing Interactive Digital Media for Jakarta's Historical Sites as a Medium for Conservation and Placemaking

Abstract: Jakarta's history spanned from the 4 th century AD, observed an intensive development during the Dutch colonial period between 17 th to the 19 th century AD, and left the Republic of Indonesia with immense infrastructural and cultural vestiges. The city, then called Batavia, was a significant political and economical center for the Dutch. Despite its importance as a living museum, many of the historical sites are now in the brink of extinction. Some were conserved, some others were converted and the rest were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Every location offers a unique experience, and mobile technology has made it even easier to share those memories. Measuring smart tourism's performance is urgent and meaningful for sustainable development [46]. Khomsi [47] states three dimensions in measuring smart city success: technology, people, and institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every location offers a unique experience, and mobile technology has made it even easier to share those memories. Measuring smart tourism's performance is urgent and meaningful for sustainable development [46]. Khomsi [47] states three dimensions in measuring smart city success: technology, people, and institutions.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, the tourism database should be improved and digitized to enhance information systems regarding customer behavior [44]. Future studies suggested by [45] should also explore challenges [46] and strategies in managing big data in the tourism industry [32].…”
mentioning
confidence: 99%
“…In 2015, the Indonesia's Ministry of Tourism identified 36 city brands from 18 provinces to promote tourism across the country. Nevertheless, studies have shown that many cities only focus on the compilation of slogans and logos without considering other aspects of tourism (Adinugroho & Mutiaz, 2012;Pakarti & Usman, 2016;Risanto & Yulianti, 2016). The impact of city branding in the context of promoting tourism and encouraging city growth has been underwhelming (Fortunata, 2014;Sugiarsono, 2009).…”
Section: 10 Introductionmentioning
confidence: 99%